Water disputes in Argentina. Analysing environmental movements against the mining industry in Mendoza, Argentina - Horn, Katharina; Armas-Diaz, Alejandro; Giraud, Marcelo (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
During the last decades, social environmental movements (SEM) and protests have been arising in response to emerg- ing social environmental conflicts that have been occurring across the globe. In contrast to the globally predominant neoliberal economic system, they fight for an alternative way of living and coping with nature and its goods and criticize persisting postcolonial power relations between countries of the Global North and South. This paper explores the claim for a right to water in terms of the right to nature, within the context of postcolonial and neoliberal structures in Men- doza, Argentina. Drawing on qualitative semi-standardized interviews with local activists and environmental experts from Mendoza as well as participatory observation and media compilation, we analyze key tools and strategies of the socio-environmental movements. The investigation points out how neoliberal restructuring processes since the end of the 20th century have triggered water conflicts in the province and in what way those are embedded in postcolonial structures.